Pathological relationships involving iron and myelin may constitute a shared mechanism linking various rare and common brain diseases. - Heidari, M.; Gerami, S.; Bassett, B.; Graham, Ross; Chua, A.; Aryal, R.; House, M.; Collingwood, J.; Bettencourt, C.; Houlden, H.; Ryten, M.; Olynyk, John; et al. (2016)
We previously demonstrated elevated brain iron levels in myelinated structures and associated cells in a hemochromatosis Hfe (-/-) xTfr2 (mut) mouse model. This was accompanied by altered expression of a group of myelin-related genes, including a suite of genes causatively linked to the rare disease family 'neurodegeneration with brain iron accumulation' (NBIA). Expanded data mining and ontological analyses have now identified additional myelin-related transcriptome changes in response to brain iron loading. Concordance between the mouse transcriptome changes and human myelin-related gene expression networks in normal and NBIA basal ganglia testifies to potential clinical relevance. These analyses implicate, among others, genes linked to various rare central hypomyelinating leukodystrophies and peripheral neuropathies including Pelizaeus-Merzbacher-like disease and Charcot-Marie-Tooth disease as well as genes linked to other rare neurological diseases such as Niemann-Pick disease. The findings may help understand interrelationships of iron and myelin in more common conditions such as hemochromatosis, multiple sclerosis and various psychiatric disorders.